Reservoirs optimization with dynamic programming - Phuong, Phan Thi Thu; Han, Dao Thi Ngoc; Lai, Hoang Van; Tri, Bui Minh (Vietnam Journal of Mechanics, 2017)
Differential Evolution (DE) and Dynamic Programming (DP) are important optimal methods in reservoir regulation. In the previous work [1], we presented the outline of DE, and applied it into Pleikrong reservoir, a big one in the Highland of Vietnam for dry season of 2010 year. Continuing from that, in this work, we present the outline of DP and then again, apply it to Pleikrong reservoir; and also apply it to Ialy, the biggest reservoir in Sesan cascade in the Highland of Vietnam; to reach optimal regulation for the maximum power production in the dry season of two years: 2010 and 2012. The results getting from DP are compared to the results by using DE. The results by these two methods have the same trend of releases which is storing the water at the beginning and significantly releasing at the end of the calculation time.